2015
DOI: 10.1093/rheumatology/kev129
|View full text |Cite
|
Sign up to set email alerts
|

Granulomatosis with polyangiitis: endoscopic management of tracheobronchial stenosis: results from a multicentre experience

Abstract: TBS represents severe and refractory manifestations with a high rate of restenosis. High-dose systemic CSs at the time of the procedure and increased time from GPA diagnosis to bronchoscopic intervention are associated with a better event-free survival. In contrast, bronchial stenoses are associated with a higher rate of restenosis than subglottic stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 19 publications
1
30
0
2
Order By: Relevance
“…There were 14 men (32%) and 30 women (68%). Epidemiologic data of this cohort confirm that GPA patients with SGS tend to be younger and more often female .…”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…There were 14 men (32%) and 30 women (68%). Epidemiologic data of this cohort confirm that GPA patients with SGS tend to be younger and more often female .…”
Section: Methodssupporting
confidence: 54%
“…Depending on the severity of clinical symptoms, apart from conventional drug therapy, various therapeutic dilative interventional or surgical procedures have been proposed for managing SGS in patients with GPA . Repeated dilative procedures are often required, as the degree of SGS worsens in the course of the disease . Therefore, close and life‐long clinical monitoring of the presence and severity of symptoms is necessary in patients with SGS.…”
Section: Introductionmentioning
confidence: 99%
“…The observed rate of 28.8% was significantly higher than that in the PR3‐ANCA–positive GPA cohort (11.0%) and was 2–3 times as high as frequencies reported in GPA by other authors (8.5%–16%) , including a previous study from our center (12%) . It has previously been reported that subglottic stenosis predominantly affects female GPA patients and patients of young age and that rates of renal involvement are lower in GPA patients with subglottic stenosis , which is consistent with our findings.…”
Section: Discussionmentioning
confidence: 82%
“…Ciclofosfamida (CYC) modificou a história natural da GPA com melhora na sobrevida e na resposta ao tratamento 1,4,22,23 . É indicada na fase de indução na doença generalizada ou com risco de dano permanente a órgãos ou risco de morte.…”
Section: Ciclofosfamidaunclassified